2015
DOI: 10.1111/hae.12792
|View full text |Cite
|
Sign up to set email alerts
|

Early prophylaxis in children with severe haemophilia A: clinical and ultrasound imaging outcomes

Abstract: A well-preserved joint status was found in our cohort. High-resolution US detected a higher percentage of abnormalities than the physical evaluation, but the clinical implications of these findings still need to be ascertained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 28 publications
(32 reference statements)
9
69
7
Order By: Relevance
“…In the study, total HJHS scores correlated with age (r=0.56, p=0.006), weight (r=0.61, p=0.002), and age at the start of prophylaxis (r=0.63; p=0.001). 22 In our study, the HJHS and HEAD-US scores were higher compared to Altisent's study 22 due to different treatment regimen, showing that prophylaxis can preserve joint function and prevent joint damage in children with severe hemophilia A.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In the study, total HJHS scores correlated with age (r=0.56, p=0.006), weight (r=0.61, p=0.002), and age at the start of prophylaxis (r=0.63; p=0.001). 22 In our study, the HJHS and HEAD-US scores were higher compared to Altisent's study 22 due to different treatment regimen, showing that prophylaxis can preserve joint function and prevent joint damage in children with severe hemophilia A.…”
Section: Discussioncontrasting
confidence: 52%
“…Recent observational study reported by Altisent et al 22 showed the utilization of HJHS and HEAD-US scores in severe hemophilia children aged 4-19 years (n=25) treated with prophylaxis treatment and no history of inhibitor. The median of prophylaxis dose was 65.4 IU/kg/week.…”
Section: Discussionmentioning
confidence: 99%
“…However, ultrasound can be observer-dependent and cannot visualize deep structures, so is not ideal for detecting subchondral cysts, loss of cartilage or haemosiderin deposits [38]. A new, standardized procedure, HEAD-US [39], aims to increase inter-rater reliability of ultrasonic evaluation of joints, although this score still requires validation. As with other assessment tools, the age of the patient and severity of MSK dysfunction should be considered when selecting an appropriate imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently reported Haemophilia Early Arthropathy Detection with UltraSound (HEAD-US) study, high-resolution ultrasonography detected a higher percentage of abnormalities than the physical evaluation and was concordant with the HJHS score in 73% of joints [26]. Differences among operators and instrument resolutions, however, can hinder comparability across treatment centres and/or across studies.…”
Section: Joint Statusmentioning
confidence: 88%